The digital extension of the psychotherapeutic field and the role of the body in online therapy: a grounded theory study with psychotherapists in training - Birgitta Schiller; Stella Becher-Urbaniak; Eva Wimmer; Lisa Winter; Kathrin Mörtl (Frontiers in Psychology, 2025)
IntroductionThe transition to online therapy has reshaped the psychotherapeutic field, introducing novel challenges and opportunities. In the digital realm, bodily perception often appears fragmented, prompting therapists to develop new ways of maintaining presence and connection. Online therapy has thus expanded therapeutic culture through distinct experiential dynamics.MethodsThis qualitative study investigated unconscious processes and bodily awareness in online therapy. Semi‑structured interviews were conducted with psychotherapy trainees at Sigmund Freud University Vienna. Data were analyzed using Grounded Theory to inductively identify central themes.ResultsFindings revealed that conscious bodily awareness plays a pivotal role in online therapeutic engagement. As trainees practiced clinically in the digital setting, they constructed a new foundation for professional development. This shift influenced not only individual competencies but also fostered what can be called a digitally mediated therapeutic habitus.DiscussionWhile co‑presence and institutional spaces remain valuable, the evolving landscape of psychotherapy calls for reimagining traditional structures. The potential of online therapy has become increasingly evident, challenging rigid notions of therapeutic space. Further research, especially on training and professional identity formation, is essential to legitimize and integrate online therapy into the broader psychotherapeutic field.